3(2y-4)=5(y+3)

Simple and best practice solution for 3(2y-4)=5(y+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2y-4)=5(y+3) equation:


Simplifying
3(2y + -4) = 5(y + 3)

Reorder the terms:
3(-4 + 2y) = 5(y + 3)
(-4 * 3 + 2y * 3) = 5(y + 3)
(-12 + 6y) = 5(y + 3)

Reorder the terms:
-12 + 6y = 5(3 + y)
-12 + 6y = (3 * 5 + y * 5)
-12 + 6y = (15 + 5y)

Solving
-12 + 6y = 15 + 5y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-5y' to each side of the equation.
-12 + 6y + -5y = 15 + 5y + -5y

Combine like terms: 6y + -5y = 1y
-12 + 1y = 15 + 5y + -5y

Combine like terms: 5y + -5y = 0
-12 + 1y = 15 + 0
-12 + 1y = 15

Add '12' to each side of the equation.
-12 + 12 + 1y = 15 + 12

Combine like terms: -12 + 12 = 0
0 + 1y = 15 + 12
1y = 15 + 12

Combine like terms: 15 + 12 = 27
1y = 27

Divide each side by '1'.
y = 27

Simplifying
y = 27

See similar equations:

| -5=x^3+3x^2-9x-13 | | -4-(-3)= | | -110+22x=-1 | | 3x^2+15x-2=0 | | -16t^2+32t+32=0 | | -8+2x=6 | | -132+11x=-3 | | 4x-10x=36 | | -y+3x+6=-5 | | 3p-2=29 | | 41k=-2747 | | 9y+4y=104 | | 5x+-6=11 | | 29+n=13 | | 4x-9=-9 | | 4a-5=15 | | X-7=-19 | | 5x=4y+28 | | 2(2y-4)=3(y+5) | | 0.4(x-9)=20 | | 1.29*x=5 | | 3x+25=17x | | X^3+9X^2+20X=0 | | X^3+2X^2-2X-4=0 | | (x+5)(4x-3)=0 | | X^4-X^3+5X^2-5X=0 | | 3y^2=-5y-2 | | 418=-22 | | 8x^3=2x | | 0+-5n=2n | | -10p+99=12 | | 9a=4b |

Equations solver categories